IL-4 downregulates expression of the target receptor CD30 in neoplastic canine mast cells - Bauer, K. (Vet Comp Oncol, 2016)
CD30 is a novel therapeutic target in human mast cell (MC) neoplasms. In this ‘comparative oncology’ study, we examined CD30 expression and regulation in neoplastic canine MC using a panel of immunomodulatory cytokines [interleukin-2 (IL-2), IL-4, IL-5, IL-6, IL-13 and stem cell factor (SCF)] and the canine mastocytoma cell lines NI-1 and C2. Of all cytokines tested IL-4 was found to downregulate expression of CD30 in NI-1 and C2 cells. We also found that the CD30-targeting antibody-conjugate brentuximab vedotin induces growth inhibition and apoptosis in both MC lines. Next, we asked whether IL-4-induced downregulation of CD30 interferes with brentuximab vedotin-effects. Indeed, pre-incubation of NI-1 cells with IL-4 decreased responsiveness towards brentuximab vedotin. To overcome IL-4-mediated resistance, we applied drug combinations and found that brentuximab vedotin synergizes with the Kit-targeting drugs masitinib and PKC412 in inhibiting growth of NI-1 and C2 cells. In summary, CD30 is a new marker and IL-4-regulated target in neoplastic canine MC.